K3Li3Gd7(BO3)9: A New Gadolinium‐Rich Orthoborate for Cryogenic Magnetic Cooling. Issue 13 (1st February 2018) - Xia, Mingjun; Shen, Shipeng; Lu, Jun; Sun, Young; Li, Rukang
Abstract: Magnetic cooling technology based on magnetocaloric effect (MCE) has attracted great interest in obtaining extremely low temperatures, for example, for space exploration. Here, we grew a new gadolinium‐rich orthoborate K3 Li3 Gd7 (BO3 )9 (1 ) as a promising cryogenic magnetic coolant. It exhibits a complicated three dimensional framework constructed from BO3 groups and gadolinium‐oxygen chains. The Gd−O chain consists of two types of clusters of Gd3 O20 and Gd3 O19 interconnection by Gd(4)O8 polyhydron. Due to its high gadolinium concentration, a large −Δ S m of 56.6 J kg −1  K −1 for1 was obtained at 2 K and Δ H =7 T, much larger than that of the commercial benchmark Gd3 Ga5 O12 (GGG) crystal (38.4 J kg −1  K −1 ), suggesting it to be an excellent MCE material. Abstract : Swimming in gadolinium : K3 Li3 Gd7 (BO3 )9, a novel gadolinium‐rich borate as promising magnetic refrigerant material, exhibits a very large magnetocaloric effect with −Δ S m of 277.2 mJ cm −3  K −1 (56.6 J kg ‐1  K −1 ), superior to the performance of benchmark Gd3 Ga5 O12 .